If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -2(-1x + 9) = -90 Reorder the terms: 7x + -2(9 + -1x) = -90 7x + (9 * -2 + -1x * -2) = -90 7x + (-18 + 2x) = -90 Reorder the terms: -18 + 7x + 2x = -90 Combine like terms: 7x + 2x = 9x -18 + 9x = -90 Solving -18 + 9x = -90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 9x = -90 + 18 Combine like terms: -18 + 18 = 0 0 + 9x = -90 + 18 9x = -90 + 18 Combine like terms: -90 + 18 = -72 9x = -72 Divide each side by '9'. x = -8 Simplifying x = -8
| -6x+3(-4x+15)=189 | | 7x-6(2x-11)=121 | | -3x+4(3x-12)=60 | | 6x+2(x-6)=52 | | (w+2)(w+11)=-18 | | (p-8)(p-2)=-5 | | 11+8x=29-x | | 9p(p+1)+13=5(2p+17)-8p | | 5p-17=5+p | | 65+41x=121x-55 | | 9+2x=-4+45 | | 9-x=14 | | 11r=0 | | 3x+2(x-1)=8 | | 3(-1x+6)=18 | | -11-5a=(5a+4) | | 5x+8=-2 | | 56-5x=4x+24 | | 10-9x=215-44x | | -41-9x=7x+23 | | (x+5)(x+2)=(x+6)+(x-1) | | 2x+10=-70-8x | | 131-5x=4x+14 | | -35-2x=10-7x | | 65-3x=9x+17 | | 4x+14=84-3x | | a+a+7+3a+a-1=42 | | 18=3(x-6) | | 5+4x=20+x | | -10=2(3v+7) | | 2x+38=10x-58 | | -3=3(x+5) |